Doula Care: A Review of Outcomes and Impact on Birth Experience. Issue 2 (February 2023) - Ramey-Collier, Khaila; Jackson, Maya; Malloy, Angela; McMillan, Cindy; Scraders-Pyatt, Andora; Wheeler, Sarahn M.
Abstract : Importance: Doulas are trained professionals that provide comprehensive support during the perinatal period. Doula-supported care is associated with improved maternal and infant outcomes including decreased preterm birth, increased breastfeeding initiation, and higher patient satisfaction. In addition, research suggests that doula support is a promising strategy to mitigate racial disparities in maternal and infant health outcomes. Objective: This article reviews doulas' scope of practice, perinatal outcomes associated with doula-assisted care, and their impact on alleviating racial disparities in maternal-infant outcomes. Evidence Acquisition: A literature search using the search engine PubMed was done. The search terms included ([Doula OR doulas OR labor coach] AND [Preterm OR prenatal care OR race OR racial OR racism OR Black OR African American]). Studies had to be written in English. Results: The search resulted 90 articles of which 18 original articles and 16 review articles were reviewed. The literature demonstrates that doula support increases vaginal delivery while decreasing preterm birth and low birth weight. Studies also show that doula support is uniquely effective for Black patients and is a promising strategy to reduce health care inequities. Conclusions and Relevance: Doulas may provide significant perinatal benefit for birthing patients and their infants, with advantages also noted for Black patients. The current article provides an overview of the literature focused on doula support. Target Audience: Obstetricians and gynecologists, family physicians Learning Objectives: After completing this activity, the learner should be better able to describe the role of doulas during labor and postpartum period; discuss the improved perinatal outcomes that are associated with doula-supported care; and identify the benefits of doula care for Black birthing individuals, who are disproportionately affected by adverse outcomes.